Impact of perioperative chemotherapy and radiotherapy in patients with primary extremity soft tissue sarcoma: retrospective analysis across major histological subtypes and major reference centres. (December 2018) - Callegaro, Dario; Miceli, Rosalba; Bonvalot, Sylvie; Ferguson, Peter; Strauss, Dirk C.; Levy, Antonin; Griffin, Anthony; Hayes, Andrew J.; Stacchiotti, Silvia; Le Pèchoux, Cecile; Smith, Myles J.; Fiore, Marco; et al.
Abstract: Background: The role of radiotherapy (RTx) and chemotherapy (CTx) in primary extremity soft tissue sarcoma (eSTS) patients is not precisely defined. Methods: All consecutive primary eSTS patients treated within three European and one North American reference centres in a 20-year time span were included. The tendency to perform chemotherapy/radiotherapy (CTx/RTx) was explored using multivariable binary logistic models. Five and 10-year overall survival (OS) and crude cumulative incidence (CCI) of local recurrence (LR) and distant metastasis (DM) were estimated. Multivariable analyses of OS, CCI of LR and CCI of DM were performed. The effect of CTx administration was explored with a propensity score matching analysis. Results: Overall, 3752 patients were included. Median follow-up was 79 months (interquartile range 44–119). Ten-year OS, CCI of LR and CCI of DM were 66.3% (64.3–68.2%), 8.2% (7.2–9.2%) and 28.2% (26.6–30.0%), respectively. Centre and histology significantly influenced administration of RTx/CTx. RTx was associated with a better local outcome, especially in myxoid liposarcoma, vascular sarcoma and myxofibrosarcoma, without being associated with survival. Chemotherapy was not an independent prognostic factor for OS in all patients (p = 0.73). In a propensity score–matched analysis, patients treated with CTx had longer survival although this difference did not reach statistical significance (p = 0.054). The use of perioperative CTx in patients with primary localised eSTS was not associated with worse survival after occurrence of DM. Conclusion: Some histologies gain a greater benefit from perioperative RTx in terms of LR risk reduction. The trend towards a 5% survival benefit associated with CTx administration is consistent with the published literature, but definitive conclusions are awaited from ongoing randomised controlled trials. Perioperative CTx for primary eSTS does not hamper post-DM survival. Highlights: The use of RTx/CTx in primary extremity soft tissue sarcomas is highly different among reference centres. Myxoid liposarcoma, vascular sarcoma and myxofibrosarcoma benefit the most from RTx. CTx administration is associated with a trend towards a 5% survival benefit. Post-distant metastasis survival is not hampered by perioperative CTx at primary.